Discourses of disorder : riots, strikes and protests in the media - Kelsey, Darren, 1983-; Hart, Christopher (Linguist) (Edinburgh University Press, 2019)
Drawing on insights from linguistics, multimodality and media studies, this book explores the ideological dimensions of media representation and its function in discursively constructing public understandings of, and attitudes toward, civil disorder.